2020
DOI: 10.1159/000506137
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of the Charles Bonnet Syndrome in Patients with Neovascular Age-Related Macular Degeneration: The Importance of Early Detection

Abstract: We investigated the characteristics, prognosis, and clinical outcome of the Charles Bonnet syndrome (CBS) in patients with neovascular age-related macular degeneration (AMD). Methods: Five hundred psychiatrically healthy patients with neovascular AMD were screened for CBS. The individuals that fulfilled the inclusion criteria were systematically interviewed using a structured questionnaire that covered the impact, prognosis, risk factors, phenomenology, symptoms, and knowledge about the syndrome. A control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…One case report found that CBS did not interfere with daily function, reflecting findings in other studies -not everyone experiences difficulties linked to visual hallucinations (Cox & Ffytche, 2014;Esteves Leandro et al, 2020). As the purpose of medical case reports is to detail the diagnostic process, in-depth exploration about how CBS effects everyday function is not a priority, or may not be reported.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…One case report found that CBS did not interfere with daily function, reflecting findings in other studies -not everyone experiences difficulties linked to visual hallucinations (Cox & Ffytche, 2014;Esteves Leandro et al, 2020). As the purpose of medical case reports is to detail the diagnostic process, in-depth exploration about how CBS effects everyday function is not a priority, or may not be reported.…”
Section: Discussionmentioning
confidence: 93%
“…Esteves Leandro et al (2020) also looked at the clinical impact of CBS, focusing on patients with neovascular age-related macular degeneration. Out of 500 eligible patients attending an eye clinic, 45 screened positive for CBS and completed a structured, face-to-face questionnaire based on Cox and Ffytche’s (2014) survey items.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, awareness of CBS among patients is limited (Singh et al 2014). When the patient is unaware of the nature of CBS, these phenomena may induce fear and anxiety (Esteves Leandro et al, 2020). It may further complicate the issue, that these experiences may be difficult to talk about given the taboo and difficulties concerning having a psychiatric disease or dementia.…”
Section: Discussionmentioning
confidence: 99%